James, Jude, 2 Peter - Sidebottom, E.M. (Grand Rapids, MI Eerdmans, 1967)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. James -- commentaries; Bible. N.T. Jude -- commentaries; Bible. N.T. Peter, 2nd -- commentaries